2012
DOI: 10.1002/smi.2443
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Stressful or Traumatic Events: What Aspects of Trauma Reactions are Associated with Health Outcomes?

Abstract: The presence of posttraumatic stress disorder (PTSD) symptoms has been shown to be related to a number of health outcomes. In the current study, we explored which specific aspects of PTSD are most related to health measures. The associations between the specific DSM-IV-TR PTSD criteria (criteria A-F) and five indicators of health and well-being--physical health symptoms, quality of life, mental health, depression and negative affect--were examined. The sample consisted of 711 undergraduates. A non-clinical sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
2
15
1
Order By: Relevance
“…Previous research indicates that the initial state of hyperarousal can become chronic for some trauma survivors, essentially causing dysregulation of the physiological stress system leading to abnormal levels of stress hormones such as cortisol and norepinephrine and the development of stress-related diseases over time (Kendall-Tackett, 2000). Although the specific pathways by which trauma leads to physical health problems is still inconclusive, recent research has indicated that hyperarousal symptoms may uniquely mediate the relationship between trauma and health symptoms (Boals, Riggs, & Kraha, 2013;Perez, Abrams, Lopez-Martinez, & Asmundson, 2012). Testing this model is beyond the scope of this paper, but our results warrant further testing of the association between PTSD symptoms and stress-related medical conditions in long-term survivors of disasters.…”
Section: Tablementioning
confidence: 98%
“…Previous research indicates that the initial state of hyperarousal can become chronic for some trauma survivors, essentially causing dysregulation of the physiological stress system leading to abnormal levels of stress hormones such as cortisol and norepinephrine and the development of stress-related diseases over time (Kendall-Tackett, 2000). Although the specific pathways by which trauma leads to physical health problems is still inconclusive, recent research has indicated that hyperarousal symptoms may uniquely mediate the relationship between trauma and health symptoms (Boals, Riggs, & Kraha, 2013;Perez, Abrams, Lopez-Martinez, & Asmundson, 2012). Testing this model is beyond the scope of this paper, but our results warrant further testing of the association between PTSD symptoms and stress-related medical conditions in long-term survivors of disasters.…”
Section: Tablementioning
confidence: 98%
“…Second, the presence of hyperarousal symptoms such as insomnia and irritability may be related to the presence of somatic complaints (Boals, Riggs, & Kraha, 2013). Additionally, there were strong correlations between AS severity and physical health issues as well as physical health quality of life.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, there is evidence that the hyperarousal symptoms (e.g., irritability, insomnia, hypervigilance) following a traumatic event mediate the relationship between trauma and physical health symptoms (Boals, Riggs, & Kraha, 2012).…”
Section: Quality Of Lifementioning
confidence: 99%
“…61 Perhaps the most well-known conception of trauma reactions is PTSD, a diagnosable mental disorder classified by the American Psychiatric Association in the Diagnostic and Statistical Manual of Mental Disorders, which requires that a person exhibit a number of trauma reactions over a specified period of time to be clinically significant. 61 Perhaps the most well-known conception of trauma reactions is PTSD, a diagnosable mental disorder classified by the American Psychiatric Association in the Diagnostic and Statistical Manual of Mental Disorders, which requires that a person exhibit a number of trauma reactions over a specified period of time to be clinically significant.…”
Section: Trauma Reactions and Adverse Outcomesmentioning
confidence: 99%
“…Trauma reactions are the specific and varied psychological, physiological, and behavioral responses that an individual might have after experiencing one or more traumas. 61 Perhaps the most well-known conception of trauma reactions is PTSD, a diagnosable mental disorder classified by the American Psychiatric Association in the Diagnostic and Statistical Manual of Mental Disorders, which requires that a person exhibit a number of trauma reactions over a specified period of time to be clinically significant. 62 Trauma reactions vary by individual and often do not rise to the level of a PTSD diagnosis.…”
Section: Trauma Reactions and Adverse Outcomesmentioning
confidence: 99%